MnCaTa2O7—a magnetically ordered polar phase prepared via cation exchange - Mallick, S; Orlandi, F; Manuel, P; Zhang, W; Halasyamani, PS; Hayward, MA (American Chemical Society, 2023)
Reaction between the pseudo-Ruddlesden-Popper phase Li2CaTa2O7 and MnCl2 at 375 °C yields MnCaTa2O7, a paramagnetic polar phase (space group P21nm), which adopts an a–b–c+/b–a–c+ distorted, layered perovskite structure. Magnetization and neutron diffraction data show that MnCaTa2O7 adopts an antiferromagnetically ordered state below TN = 56 K and exhibits large lattice parameter anomalies and a transient increase in its polar distortion mode at TA = 50 K. However, in contrast to the related phase MnSrTa2O7, MnCaTa2O7 shows no strong signature of weak ferromagnetism and thus shows no signs of magnetoelectric coupling. The differences in physical behavior between the two MnATa2O7 phases appear to be related to their differing Mn cation-order and differing TaO6 tilting schemes and demonstrate that even subtle changes to these orderings can have large effects on the distortion-mode couplings, which drive complex behavior of this class of “hybrid improper” ferroelectric material.